A reverse engineering technique for creating virtual robots - Brezovnik, Simon (Strojniški vestnik, 2009)
A novel system for out-of-date robotic systems that are not interesting for use any more is introduced. We give a solution for revitalization of these robotic systems with upgrading the programming software from on-line programming to indirect virtual programming and virtual modelling of a production cell equipped with robots. Direct and inverse kinematic models of the robot ACMA XR 701 in the virtual space were developed with reverse engineering technologies.
Keywords: robotika; programiranje; modeliranje; robotska celica